2022
DOI: 10.3390/ijerph19031685
|View full text |Cite
|
Sign up to set email alerts
|

Football and Zumba Training in Female Hospital Staff: Effects after 12 and 40 Weeks on Self-Reported Health Status, Emotional Wellbeing, General Self-Efficacy and Sleep Problems

Abstract: Background: This 40-weeks intervention study evaluates the effects on self-reported health status, emotional wellbeing, general self-efficacy and sleep problems among female hospital employees. Methods: 107 employees were cluster-randomized into three groups; football (FG), Zumba (ZG) and control (CG). Outcome measurements were conducted at baseline, 12 and 40 weeks. Weekly training frequencies in the first 12 and next 28 weeks were 2.4 ± 0.3 and 0.8 ± 0.2 in FG and 2.3 ± 0.3 and 0.9 ± 0.2 in ZG. Results: Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…All studies were of low to moderate quality. Nineteen studies were randomised controlled trials (RCTs) [ 62 75 ], and eight were non-RCTs [ 76 83 ]. Of the 19 RCTs, only 2 studies clearly stated that participants were blinded [ 64 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies were of low to moderate quality. Nineteen studies were randomised controlled trials (RCTs) [ 62 75 ], and eight were non-RCTs [ 76 83 ]. Of the 19 RCTs, only 2 studies clearly stated that participants were blinded [ 64 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Barene et al found that soccer improved the self-efficacy and emotional wellbeing of hospital employees after 12 weeks compared with Zumba; however, the improvements were equivalent by the end of the 40-week intervention [ 62 ]. Soccer or volleyball also improved depressive symptoms compared with aerobic dance in tertiary students [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…The following interventions did not enhance well-being among healthcare workers: mindful colouring of mandalas for 10 days [ 44 ]; a 40-week football or Zumba training course for an hour per session, 2–3 times per week [ 45 ]; an intervention of 22 text messages about factors associated with burnout in a period of 10 months [ 46 ]; a small-group intervention based on theory of successful ageing for mental health promotion [ 37 ]; an 8-week relaxation meditation course [ 47 ]; in-person mindfulness resilience training or smartphone-delivered resilience training [ 48 ]; an 8- to 12-week online multi-component positive psychology intervention of psychoeducation and positive psychology exercises [ 49 ]; and a 3-h community resiliency training course (psychoeducation and sensory awareness skills) [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine RCTs assessed how workplace interventions affect perceived general health ( Table S1 ). A 40-week Zumba training program (one hour per session and 2–3 sessions per week) [ 45 ], an 8-week cultural participation program (films, concerts, art exhibitions, or choir singing) [ 51 ], and a 5-day course on role-playing/simulation and discussion of strategies to deal with work stressors and stressful situations [ 52 ] improved self-rated health among healthcare workers, but the effects were small [ 45 , 51 ]. A 12-week mobile wellness program to promote physical activity and improve sleep quality enhanced wellness among female nurses working rotating shifts [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously documented physiological health improvements after both football and Zumba exercise (Barene et al, 2013; Barene et al, 2014a), which may be a potential explanation for the observed lower number of sick days in the last period of sick leave as well as number of sick days due to general health problems past four weeks. Moreover, as regular physical activity is associated with beneficial self‐reported health, self‐efficacy and well‐being, this may represent potential factors explaining the observed positive effects on sick leave days (Barene & Krustrup, 2022). Furthermore, as previous studies have suggested that social relations may affect sick leave (Löve et al, 2012; Melchior et al, 2003; Rydström et al, 2017), another explanation may be increased perceived social affiliation through participation in group‐based exercises.…”
Section: Discussionmentioning
confidence: 99%